Effect of strength training on the functional capacity of active elderly: systematic review (Research, Society and Development, 2021)
The study purpose was to systematically review the effect of strength training on the active elderly functional capacity. The search was carried out in the Scielo, MedLine and Lilacs indexing databases, as well as in the PEDro and Google Academic repositories between 2010 and 2020. The following descriptors were used to search in different combinations: ‘strength training’ or ‘resistance training’ and ‘elderly’ and ‘functional capacity’. Fourteen studies were included in the present review, which showed improvement in the functional capacity of elderly people after strength training intervention. Strength training protocols as a form of intervention in an elderly and active population are able to improve functional capacity by increasing muscle mass and strength, bone mineral density and functional capacity. It is concluded that strength training is able to improve the functional capacity of elderly people. In addition, the training proposal demonstrated optimization of balance, gait, bone mineral density and muscle mass in elderly individuals.